A survey study of attitudes toward, and preferences for, e‐therapy interventions for eating disorder psychopathology. Issue 6 (2nd April 2020) - Linardon, Jake; Shatte, Adrian; Tepper, Hannah; Fuller‐Tyszkiewicz, Matthew
Abstract: Objective: E‐therapy shows promise as a solution to the barriers that stand in the way of people receiving eating disorder (ED) treatment. Despite the potential for e‐therapy to reduce the well‐known treatment gap, little is known about public views and perspectives on this mode of intervention delivery. This study explored attitudes toward, and preferences for, e‐therapy among individuals spanning the spectrum of eating pathology. Method: Survey data assessing e‐therapy attitudes and preferences were analyzed from 713 participants recruited from the public. Participants were categorized into one of five subgroups based on the type of self‐reported ED symptoms and severity/risk level, ranging from high risk to a probable threshold or subthreshold ED. Results: Attitudes toward e‐therapies appeared to be relatively positive; participants largely supported health care insurance coverage of costs for e‐therapies, and were optimistic about the wide‐ranging benefits of e‐therapy. Although three‐quarters of participants expressed a preference for face‐to‐face therapy, a significant percentage of participants (∼50%) reported an intention to use an e‐therapy program for current or future eating problems, with intention ratings highest (70%) among those with probable bulimia nervosa (BN). Variables associated with an e‐therapy preference were not currently receiving psychotherapy, more positive e‐therapy attitudes, and greater stigma associated with professional help‐seeking. Variables associated with e‐therapy intentions were more positive e‐therapy attitudes and a probable BN classification. Conclusions: Present findings have important implications for increasing online intervention acceptance, engagement, and help‐seeking among those at different stages of illness.